Subthalamic nucleus deep brain stimulation in isolated dystonia: A 3-year follow-up study. (3rd January 2017) - Ostrem, Jill L.; San Luciano, Marta; Dodenhoff, Kristen A.; Ziman, Nathan; Markun, Leslie C.; Racine, Caroline A.; de Hemptinne, Coralie; Volz, Monica M.; Heath, Susan L.; Starr, Philip A.
Abstract : Objective: To report long-term safety and efficacy outcomes of a large cohort of patients with medically refractory isolated dystonia treated with subthalamic nucleus (STN) deep brain stimulation (DBS). Methods: Twenty patients (12 male, 8 female; mean age 49 ± 16.3 years) with medically refractory isolated dystonia were studied (14 were followed for 36 months). The primary endpoints were change in Burke-Fahn-Marsden Dystonia Rating Scale (BFMDRS) motor score and Toronto Western Spasmodic Torticollis Rating Scale (TWSTRS) total score at 36 months compared to preoperative baseline. Multiple secondary outcomes were also assessed (ClinicalTrials.gov NCT00773604). Results: Eighteen of 20 patients showed improvement 12 months after STN DBS with sustained benefit persisting for 3 years (n = 14). At 36 months, BFMDRS motor scores improved 70.4% from a mean 17.9 ± 8.5 to 5.3 ± 5.6 ( p = 0.0002) and total TWSTRS scores improved 66.6% from a mean 41.0 ± 18.9 to 13.7 ± 17.9 ( p = 0.0002). Improvement at 36 months was equivalent to that seen at 6 months. Disability and quality of life measures were also improved. Three hardware-related and 24 stimulation-related nonserious adverse events occurred between years 1 and 3 (including 4 patients with dyskinesia). Conclusions: This study offers support for long-term tolerability and sustained effectiveness of STN DBS in the treatment of severe forms of isolated dystonia. Classification of evidence: This study provides Class IV evidence that STN DBS decreases long-term dystonia severity in patients with medically refractory isolated dystonia.